2018
DOI: 10.17679/inuefd.336990
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Creative Writing Studies on Attitudes towards Writing and the Creative Writing Success

Abstract: The aim of this study was to determine the effect of creative writing activities on writing attitudes and the success of creative writing. The pre-test and post-test control group experimental design has been used in the study. In the study group, 50 students from the fifth grade of Gazi Secondary School in Bartın city center were located. The attitudes towards writing were determined by the Writing Attitude Scale. Creative writing success was determined by student compositions. Student compositions were score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
2
0
5
Order By: Relevance
“…Upon examining the post-test scores of the experimental and control groups in the study, a significant difference favoring the experimental group was identified. Literature also shows findings that alternative writing activities positively affect students' creative writing skills (Austen, 2005;Beydemir, 2010;Demirbaş & Şahin, 2023;Duru & İşeri, 2015;Erdoğan & Çelikpazu, 2020;Kasap, 2018;Kolaç, 2009;Medd, Hills & Houtz, 2003;Özdemir & Çevik, 2018;Susar Kırmızı, 2008;Şahin & Ata, 2023). Similarly, Duru and İşeri (2015) found that the post-test scores of the experimental group, which was subjected to creative writing techniques, were significantly different from those of the control group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Upon examining the post-test scores of the experimental and control groups in the study, a significant difference favoring the experimental group was identified. Literature also shows findings that alternative writing activities positively affect students' creative writing skills (Austen, 2005;Beydemir, 2010;Demirbaş & Şahin, 2023;Duru & İşeri, 2015;Erdoğan & Çelikpazu, 2020;Kasap, 2018;Kolaç, 2009;Medd, Hills & Houtz, 2003;Özdemir & Çevik, 2018;Susar Kırmızı, 2008;Şahin & Ata, 2023). Similarly, Duru and İşeri (2015) found that the post-test scores of the experimental group, which was subjected to creative writing techniques, were significantly different from those of the control group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Elde edilen bu bulgu, uygulanan programın öğrencilerin bir konuyu ve o konu ile ilgili farklı düşünceleri cümle ve paragraflara göre düzenleyerek yazma sürecinin bileşenlerini dikkate alarak anlam bütünlüğü olan metinler oluşturmada etkililiğini ortaya koymaktadır. Bu bulgu, alanyazında yaratıcı yazma temelli diğer çalışmaların bulgularıyla paralellik göstermektedir (Akbaba, 2020;Beydemir, 2010;Kolikpınar, 2021;Nasir, Naqvi ve Bhamani, 2013;Pardlow, 2003). Alkaaf ve Al-Bulushi (2017) yapmış oldukları çalışmada öykü anlatımı ile yapılan yazma eğitiminin 7. sınıf öğrencilerinin öyküleyici metin yazma becerileri üzerinde etkili olduğunu tespit etmişlerdir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Tok ve Kandemir (2015) tarafından yapılan araştırma da yaratıcı yazma etkinliklerinin yazma eğilimi üzerinde olumlu bir etkisi olduğunu göstermektedir. Özdemir ve Çevik (2018), Demirci ve Altinay (2021), Beydemir (2010) ve Korkmaz (2015) tarafından yapılan ve yaratıcı yazma yaklaşımına dayalı çalışmaların öğrencilerin yazmaya yönelik tutumlarını olumlu yönde etkilediği tespit edilmiştir. Özdemir ve Çevik ( 2018)'e göre yazmaya yönelik olumlu tutuma sahip olmak yazma eğitiminin amaçlarını yerine getirme ve yazma başarısını artımada oldukça önemli bir yere sahiptir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Alan yazına bakıldığında yaratıcı yazma ile ilgili yapılan çalışmaların sonucunda, yaratıcı yazma çalışmalarının öğrencilerin yazma becerisine olumlu katkılar sağladığı belirlenmiştir. Buna göre yaratıcı yazma etkinlikleri, öğrencilerin kendilerini yazma sürecinde daha rahat hissederek yazmaya karşı daha ilgili olmasını sağlamakta ve yazma performanslarını arttırmada katkı sağlamaktadır (Kırmızı, 2009;Beydemir, 2010;Duran, 2010;Ak, 2011;Akkaya,2011;Temizkan, 2011;Demir, 2012;Kırmızı ve Beydemir, 2012;Avcı, 2013;Erdoğan ve Yangın, 2014;Korkmaz, 2015;Özdemir ve Çevik, 2018;Şahin, 2019;Erdoğan ve Ekinci Çelikpazu, 2020;Türkyılmaz ve Arı, 2021). Ayrıca alan yazında gerek yabancılara Türkçe öğretiminde gerekse ana dili olarak Türkçe öğretimi alanında yapılan karikatür konulu çalışmalar, materyal olarak karikatür kullanımının Türkçe eğitimine olumlu katkılar sağladığı belirlenmiştir.…”
Section: Introductionunclassified